2009
DOI: 10.1364/oe.17.019414
|View full text |Cite
|
Sign up to set email alerts
|

Optical mirror trap with a large field of view

Abstract: Holographic optical tweezers typically require microscope objectives with high numerical aperture and thus usually suffer from the disadvantage of a small field of view and a small working distance. We experimentally investigate an optical mirror trap that is created after reflection of two holographically shaped collinear beams on a mirror. This approach combines a large field of view and a large working distance with the possibility to manipulate particles in a large size range, since it allows to use a micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 14 publications
3
72
0
Order By: Relevance
“…The ultrasonic field is set up in a square capillary which is held between a glass slide and an optical mirror backed with a PZT transducer, as shown schematically in Figure 9. The mirror allows a laser source, placed below this setup, to act like a dual beam trap 54 , and allows optical manipulation from a large working distance. In this trap, radial optical trapping is due to the lateral gradient force, while axially it is the balancing of the scattering forces.…”
Section: Optical Forcesmentioning
confidence: 99%
“…The ultrasonic field is set up in a square capillary which is held between a glass slide and an optical mirror backed with a PZT transducer, as shown schematically in Figure 9. The mirror allows a laser source, placed below this setup, to act like a dual beam trap 54 , and allows optical manipulation from a large working distance. In this trap, radial optical trapping is due to the lateral gradient force, while axially it is the balancing of the scattering forces.…”
Section: Optical Forcesmentioning
confidence: 99%
“…Counterpropagating diverging beams can also be used to trap objects by using opposing objective lenses 39,40 or using a dichroic sample slide or mirror behind the sample. 41,42 The scattering forces from a pair of beams cancel when the object is centered axially, removing the requirement for high NA. This enables the use of long working distance objectives at low magnifications.…”
Section: Trapping Capabilitiesmentioning
confidence: 99%
“…The need for a high numerical aperture for stable axial trapping has confined HOT to situations where samples could be accessed using short working distance objectives. Using a mirror trap configuration [9,10] and a diamond anvil cell (DAC) [11] we have recently shown that the full power of holographic tweezers can be also made available for high pressure studies [12,13]. Optical tweezers have been successfully applied to the study of the mechanical and rheological response of soft and biological matter [14].…”
Section: Introductionmentioning
confidence: 99%